2022
DOI: 10.3389/fpls.2022.1068969
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the TCP gene family and their expression pattern in Cymbidium goeringii

Abstract: TCP gene family are specific transcription factors for plant, and considered to play an important role in development and growth. However, few related studies investigated the TCP gene trait and how it plays a role in growth and development of Orchidaceae. In this study, we obtained 14 TCP genes (CgTCPs) from the Spring Orchid Cymbidium goeringii genome. The classification results showed that 14 CgTCPs were mainly divided into two clades as follows: four PCF genes (Class I), nine CIN genes and one CYC gene (Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…Our study found some AsTCP genes (19 genes, about 39%) did not contain introns. This structural feature is similar to that found in Camellia sinensis (87%) ( Shang et al., 2022 ), Cymbidium goeringii (57%) ( Liu D. et al., 2022 ), and Dactylis glomerata (18%) ( Wang C. et al, 2023 ). Most AsTCP genes do not have introns, meaning their transcription times are shorter than those containing introns.…”
Section: Discussionsupporting
confidence: 84%
“…Our study found some AsTCP genes (19 genes, about 39%) did not contain introns. This structural feature is similar to that found in Camellia sinensis (87%) ( Shang et al., 2022 ), Cymbidium goeringii (57%) ( Liu D. et al., 2022 ), and Dactylis glomerata (18%) ( Wang C. et al, 2023 ). Most AsTCP genes do not have introns, meaning their transcription times are shorter than those containing introns.…”
Section: Discussionsupporting
confidence: 84%
“… 1 , 5 , 11 , 13 , 15 , 22 , 24 , 26 , 51 , 54 , 55 Genome-wide identification of the TCP gene family had been accomplished in several plants. 8 , 14 , 56–61 However, genome-wide characterization of the TCP gene family had not been conducted in kiwifruit. Here, we conducted the comprehensive genome-wide identification and characterization of the TCP gene family in two kiwifruit species (Ac and Ae), comparing their characters and evolutionary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The median tepal is typically modified into the labellum, which is often in the abaxial position because the inflorescence droops or the pedicel twists [ 129 ]. Many CYC -like genes in Phalaenopsis and Cattleya trianae have been identified and observed to influence floral or inflorescence development [ 130 , 131 , 132 ].…”
Section: Progress In Research On Cyc -Like Genes I...mentioning
confidence: 99%
“…Hence PeCIN8 may be crucial for orchid ovule development because of its regulatory effects on cell division. In addition, Liu et al recently identified 10 ECE clade genes ( CgCIN s and CgCYC s) from the Cymbidium goeringii genome and observed that flower-specific gene expression may be associated with the regulation of flower development [ 131 ].…”
Section: Progress In Research On Cyc -Like Genes I...mentioning
confidence: 99%